Prevalence of colistin-resistant Escherichia coli in foods and food-producing animals through the food chain: A worldwide systematic review and meta-analysis - Lencina, Florencia Aylen; Bertona, Matías; Stegmayer, María Angeles; Olivero, Carolina Raquel; Frizzo, Laureano Sebastián; Zimmermann, Jorge Alberto; Signorini Porchiett, Marcelo Lisandro; Soto, Lorena Paola; Zbrun, María Virginia (Elsevier, 2024)
The purpose of this systematic review and meta-analysis was to summarize the available scientific evidence on the prevalence of colistin-resistant Escherichia coli strains isolated from foods and food-producing animals, the mobile colistin-resistant genes involved, and the impact of the associated variables. A systematic review was carried out in databases according to selection criteria and search strategies established a priori. Random‐effect meta‐analysis models were fitted to estimate the prevalence of colistin-resistant Escherichia coli and to identify the factors associated with the outcome. In general, 4.79% (95% CI: 3.98%–5.76%) of the food and food-producing animal samples harbored colistin-resistant Escherichia coli (total number of colistin-resistant Escherichia coli/total number of samples), while 5.70% (95% confidence interval: 4.97%–6.52%) of the E. coli strains isolated from food and food-producing animal samples harbored colistin resistance (total number of colistin-resistant Escherichia coli/total number of Escherichia coli isolated samples). The prevalence of colistin-resistant Escherichia coli increased over time (P < 0.001). On the other hand, 65.30% (95% confidence interval: 57.77%–72.14%) of colistin resistance was mediated by the mobile colistin resistance-1 gene. The mobile colistin resistance-1 gene prevalence did not show increases over time (P = 0.640). According to the findings, other allelic variants (mobile colistin resistance 2–10 genes) seem to have less impact on prevalence. A higher prevalence of colistin resistance was estimated in developing countries (P < 0.001), especially in samples (feces and intestinal content, meat, and viscera) derived from poultry and pigs (P < 0.001). The mobile colistin resistance-1 gene showed a global distribution with a high prevalence in most of the regions analyzed (>50%). The prevalence of colistin-resistant Escherichia coli and the mobile colistin resistance-1 gene has a strong impact on the entire food chain. The high prevalence estimated in the retail market represents a potential risk for consumers' health. There is an urgent need to implement based-evidence risk management measures under the “One Health” approach to guarantee public health, food safety, and a sustainable future.